PEMETAAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA MELALUI PENDIDIKAN UNTUK PEMBANGUNAN BERKELANJUTAN - hendrayani, Yani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Universities struggle with interdisciplinary education for sustainable development. SDG 4.7 promotes sustainable development education to develop leaders. Sustainable development includes economic prosperity, equitable resource distribution, energy use, health and environmental awareness, and global environmental issues like climate change, biodiversity loss, poverty, etc. Permata Sari students' CSR and community development are assessed. Local SDG 2030 implementation maps diverse development issues. There are 33 Indonesian university students participate in Permata Sari online student exchange. Concept mapping enhances learning, thinking, and action. Fieldwork requires observation and data collection. Adult learning theory and content/situation analysis are used. Experiential learning is mandatory for students. Students observe local development issues and use problem-solving theory to solve them. student-environment interaction. Students' observations, interviews, and other data promote campus sustainability. Indonesian province concept maps summarize the findings. This course encourages sustainability. Sustainable development education on Indonesian campuses uses issue mapping to develop the concept map.